ANALISIS PENERIMAAN DAN EFEKTIVITAS RETRIBUSI TERMINAL TERHADAP PENDAPATAN ASLI DAERAH DI KOTA AMBON TAHUN 2014-2018 - Dwi Kriswantini (Fakultas Ekonomi dan Bisnis Universitas Pattimura, 2021)
Abstract:This study, aims to determine the growth of terminal user fees from 2014 to 2018, the effectiveness of terminal user fees from 2014 to 2018, the contribution of terminal user fees. Secondary data type, data source from the Department of Transportation and the Ambon City Revenue Office. Data collection techniques through documentation. Analysis of the data used is the analysis of growth, effectiveness and contribution. The results of data analysis show that (1) the growth of revenue from parking fees in Ambon City in 2015 was (10.43%); in 2016 amounted to 3.82%; in 2017 24.82%; this means that growth is positive while in 2018 the growth is negative at only 0.53%. (2) The effectiveness of station retribution receipts in Ambon City from 2014 to 2018 reached an average of 87.75% per year. This shows that the acceptance of Station charges in Ambon city is not effective. (2) Contribution of Station Retribution Receipts to Regional Original Revenues amounted to 3.03% in 2014; 2.34% in 2015; 2.31% in 2016; 2.59% in 2017, while in 2018 there was a decrease of 0.24% to 2.35% from 2017. Keywords: Reception, Effectiveness, Retribution, Region Original Income